2017
DOI: 10.18632/oncotarget.18074
|View full text |Cite
|
Sign up to set email alerts
|

Wip1 is associated with tumorigenity and metastasis through MMP-2 in human intrahepatic cholangiocarcinoma

Abstract: Wip1 has been shown to correlate with the metastasis/invasion of several tumors. This study was designed to investigate the clinical significance and biological function of Wip1 in intrahepatic cholangiocarcinoma (ICC). The expression of Wip1 was investigated in sixty human ICC biopsy samples by immunohistochemistry. Transient and stable knockdown of Wip1 in two human ICC cells (ICC-9810 and SSP25) were established using short hairpin RNA expression vector. Immunohistochemistry revealed that Wip1 was up-regula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 46 publications
6
20
0
Order By: Relevance
“…Our previous findings indicate that Wip1 is involved in the tumorigenicity and invasion of human ICC at least in part through the MMP-2 signaling pathway [17]. Our further data show that both iNOS and Wip1 promote ICC cell migration and invasion by up-regulating MMP expression [18].…”
Section: Discussionsupporting
confidence: 49%
See 4 more Smart Citations
“…Our previous findings indicate that Wip1 is involved in the tumorigenicity and invasion of human ICC at least in part through the MMP-2 signaling pathway [17]. Our further data show that both iNOS and Wip1 promote ICC cell migration and invasion by up-regulating MMP expression [18].…”
Section: Discussionsupporting
confidence: 49%
“…Accumulating studies identified that high Wip1 expression disrupted the homeostasis maintained by the p38 MAPK-p53-Wip1 pathway, which caused downstream Wnt-p53 inactivation through p38 MAPK dephosphorylation, and promoted the development of malignant in humans by reducing p16 protein levels [33,34]. Our previous data have indicated that Wip1 is oncogenic and is involved in invasive growth in renal cancer cells and ICC cells [12,17]. Our data also show Wip1 involved in the tumorigenicity and invasion of human ICC in part through the MMP-2 signaling pathway [17].…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations